2023
DOI: 10.3389/fphar.2023.1118788
|View full text |Cite
|
Sign up to set email alerts
|

Influence of continuous renal replacement therapy on the plasma concentration of tigecycline in patients with septic shock: A prospective observational study

Abstract: Objective: The influence of continuous renal replacement therapy (CRRT) on the steady-state plasma concentration of high-dose tigecycline was investigated in septic shock patients to provide references for drug dosing.Methods: In this prospective observational study, 17 septic shock patients presenting with severe infections needing a broad-spectrum antibiotic therapy with high-dose tigecycline (100 mg per 12 h) in the intensive care unit were included and divided into CRRT group (n = 6) or non-CRRT group (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Based on blood concentration monitoring and prescription review analysis, the results of the present study suggested that, for the rational use of tigecycline, the first dose should be administered with loading (double dose), so that the steady-state trough concentration can be reached quicker (19). This approach may improve efficacy and reduce the chance of drug resistance.…”
Section: Discussionmentioning
confidence: 90%
“…Based on blood concentration monitoring and prescription review analysis, the results of the present study suggested that, for the rational use of tigecycline, the first dose should be administered with loading (double dose), so that the steady-state trough concentration can be reached quicker (19). This approach may improve efficacy and reduce the chance of drug resistance.…”
Section: Discussionmentioning
confidence: 90%
“…26 Furthermore, a pharmacokinetic study of patients with septic shock showed that the area under the concentration-time curve for tigecycline, calculated based on trough levels, was higher in patients on CRRT than in other patients. 27 Several studies have demonstrated renal dysfunction as a risk factor for various adverse tigecycline-related events, such as hypofibrinogenemia and pancreatitis. 28,29 Possibly, renal dysfunction also predisposes patients to hypoglycemia during tigecycline therapy by causing drug overexposure.…”
Section: Discussionmentioning
confidence: 99%